2020
DOI: 10.34172/joddd.2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of vitamins C and E on experimentalorthodontic tooth movement

Abstract: Background. This experimental study aimed to assess the effects of Vitamins C and E on orthodontictooth movement. Methods. Fifty-one male Wistar albino rats were divided into six groups: five appliance groups and onecontrol group. The appliance groups had an orthodontic appliance consisting of a closed-coil springligated between the maxillary incisor and maxillary first molar (50 g). Vitamin E and C (150 mg/kg)were injected intraperitoneally per day in the first and second groups, respectively. Vitamins E an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…e administration of vitamin C and vitamin E during orthodontic treatment has confirmed positive effects on bone regeneration and can be used to accelerate the process of OTM [28]. Another study showed that injection of asperosaponin VI may enhance OTM by increasing the osteoclastic activity and inducing bone resorption at the pressure side.…”
Section: Discussionmentioning
confidence: 98%
“…e administration of vitamin C and vitamin E during orthodontic treatment has confirmed positive effects on bone regeneration and can be used to accelerate the process of OTM [28]. Another study showed that injection of asperosaponin VI may enhance OTM by increasing the osteoclastic activity and inducing bone resorption at the pressure side.…”
Section: Discussionmentioning
confidence: 98%